Segment‐Scale Seismicity of the Ultraslow Spreading Knipovich Ridge - Meier, Michaela; Schlindwein, Vera; Scholz, John‐Robert; Geils, Jonah; Schmidt‐Aursch, Mechita C.; Krüger, Frank; Czuba, Wojciech; Janik, Tomasz; Schlindwein, Vera; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Scholz, John‐Robert; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Geils, Jonah; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; Schmidt‐Aursch, Mechita C.; 1 Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany; et al. (Geochemistry, Geophysics, Geosystems, 2021)
Ultraslow spreading ridges form the slowest divergent plate boundaries and exhibit distinct spreading processes in volcanically active magmatic sections and intervening amagmatic sections. Local seismicity studies of ultraslow spreading ridges until now cover only parts of segments and give insight into spreading processes at confined locations. Here, we present a microseismicity data set that allows to study spreading processes on the scale of entire segments. Our network of 26 ocean bottom seismometers covered around 160 km along axis of the ultraslow spreading Knipovich Ridge in the Greenland Sea and recorded earthquakes for a period of about 1 year. We find seismicity varying distinctly along‐axis. The maximum earthquake depths shallow over distances of 70 km toward the Logachev volcanic center. Here, swarm activity occurs in an otherwise aseismic zone. Melts may thus be guided along the subparallel topography of the lithosphere‐asthenosphere boundary toward major volcanic centers explaining the uneven along‐axis melt distribution typical for ultraslow ridges. Absence of shallow seismicity in the upper 8 km of the lithosphere with a band of deep seismicity underneath offsets presumably melt‐poor regions from magma richer sections. Aseismic deformation in these regions may indicate weakening of mantle rocks by alteration. We do not find obvious indications for major detachment faulting that characterizes magma‐poor spreading at some ultraslow spreading segments. The highly oblique spreading of Knipovich Ridge may be the reason for a fine‐scale segmentation of the seismic activity with zones of weak seismicity possibly indicating transform motion on short obliquely oriented faults. Plain Language Summary: At mid‐ocean spreading ridges, tectonic plates drift apart and new seafloor is built by upwelling magma. The slowest spreading ridges do not receive enough magma to build new seafloor along the entire ridge. Rather, they show widely spaced volcanic centers with magma‐poor areas in‐between. The study of ...